Experimenting the Energy Economic Variables Regarding the Long-Haul Consequences on Indonesia using Vector Error Correction Model - Saudi, Mohd Haizam Mohd; Sinaga, Obsatar; Roespinoedji, Djoko; Tarofder, Arun Kumar (International Journal of Energy Economics and Policy, 2019)
The Indonesian economy has recorded solid growth in the course of recent decades, and as of late, the firm pace of economic expansion has been joined by decreased yield instability and moderately stable inflation. As a sort of rare characteristic capital, energy makes increasingly more clear imperative consequences for economic growth. Furthermore, energy consumption is the real wellspring of greenhouse gas emissions. This achieves the issues of the connections among energy economic variables, which is deserving of long-haul consideration between human capital, energy consumption, CO2 emissions, and economic growth in Indonesia. As a close neighbour, Australia has long had critical exchange ties with Indonesia. The effect of various types of energy consumption and human capital on per capita GDP growth. The information utilized world development indicator has acquired from the World Bank database amid 1985-2017. The examination technique utilized vector error correction model. In this mainly three tests are conducted in order to know the relationship among variables which is unit root test, co-integration and temporal Granger causality the outcomes show that apportioning consumption energy and controlling carbon emissions, are probably going to have no antagonistic impact on the genuine GDP per capita. In the meantime, empirically, the development of human capital has the effect on controlling CO2 emissions and energy consumption in Indonesia. Keywords: Economic, growth, energy, emission, consumption, carbon-di-oxide, human capital, vector error correction model JEL Classifications: Q55, Q50, O34 DOI: https://doi.org/10.32479/ijeep.8695